PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, MOTIVASI GURU, DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU DI SEKOLAH KHUSUS SWASTA KABUPATEN TANGERANG - Tasya Aulia Putri; Yulita Pujilestari; Imas Masriah (STKIP Subang, 2026)
This study aims to analyze the influence of principal leadership, teacher motivation, and organizational culture on teacher performance in Private Special Schools in Tangerang Regency. The study employed a quantitative approach with an associative research design. The research population consisted of 162 teachers, with a sample of 116 respondents determined using the Slovin formula through a simple random sampling technique. Data were collected using a closed-ended questionnaire developed based on the indicators of each variable and measured using a Likert scale. The data were analyzed using IBM SPSS Statistics version 27 through simple linear regression and multiple linear regression analyses after meeting the classical assumption tests. The results indicate that principal leadership, teacher motivation, and organizational culture have a positive and significant effect on teacher performance, both partially and simultaneously. These findings confirm that improving teacher performance in Private Special Schools in Tangerang Regency is strongly influenced by effective principal leadership, high levels of teacher motivation, and a conducive and sustainable organizational culture.